Standard Interferon in the Treatment of Hepatitis C; Response Rate in Genotypes 2 and 3 from an Area in Azad Kashmir, Towards North of Pakistan (Medical Forum Monthly, 2024)
Objective: To assess the response rate and side effect profile of combination therapy with standard interferon alpha 2a and ribavirin in patients with chronic hepatitis C, genotype 2 and 3.Study Design: Observational studyPlace and duration of Study: This study was conducted at Saleem Medical Complex and Maryam Maternity home, Kotli, Azad Kashmir from January 2012 to December 2012.Materials and Methods: Both male and female patients above 20 years of age with chronic hepatitis C, living in district Kotli Azad Kashmir, not treated previously, were included in the study. Viral load and genotyping were determined before initiation of treatment. Therapy was given with conventional interferon alpha 2a, 3 Million international units subcutaneously on alternate days and ribavirin 400mg tablets twice daily, for 24 weeks. PCR was repeated at the end of treatment and six months later. Clinical and lab monitoring was done at regular intervals and side effect profile was recorded.Results: Out of 150 patients, 30 (20%) were males and 120 (80%) were females. Most of the patients were between 20-50 years of age (83.99%). End of treatment response was 82% and sustained viral response was 65.33%. Fever was the most common side effect followed by flu like symptoms. All the patients completed the treatment without any dropout.Conclusion: The study showed a good response rate to standard interferon plus low dose ribavirin against genotype 2 and 3, with a favorable side effect profile without any drop out, indicating that it is a suitable treatment option.